Run-time adaptation for reconfigurable embedded processors - Bauer, Lars
Run-time Adaptation for Reconfigurable Embedded Processors by: Lars Bauer Jörg Henkel Embedded processors are the heart of embedded systems. Reconfigurable embedded processors comprise an extended instruction set that is implemented using a reconfigurable fabric (similar to a field-programmable gate array, FPGA). This book presents novel concepts, strategies, and implementations to increase the run-time adaptivity of reconfigurable embedded processors. Concepts and techniques are presented in an accessible, yet rigorous context. A complex, realistic H.264 video encoder application with a high demand for adaptivity is presented and used as an example for motivation throughout the book. A novel, run-time system is demonstrated to exploit the potential for adaptivity and particular approaches/algorithms are presented to implement it. Presents a new approach to increase the adaptivity of embedded processors; Describes a novel approach to increasing the adaptivity for reconfigurable processors, explained in a very visual/imaginable manner, as well a very precise/formal manner; Presents a complex, realistic H.264 video encoder application with a high demand for adaptivity and uses that example for motivation/in-depth evaluation throughout the book; Describes a novel run-time system that exploits the potential for adaptivity and particular approaches/algorithms to implement it.